Effect of Starter Culture and Low Concentrations of Sodium Nitrite on Fatty Acids, Color, and Escherichia coli Behavior during Salami Processing - Carla María Blanco-Lizarazo; Indira Sotelo-Díaz; José Luis Arjona-Roman; Adriana Llorente-Bousquets; René Miranda-Ruvalcaba (International Journal of Food Science)
The reduction of NaNO2 and safety in meat products have been a concern to the meat industry for the last years. This research evaluated the changes in total fatty acids (TFAs) and myoglobin forms by adding starter culture (Lactobacillus sakei/Staphylococcus carnosus) and 50 ppm of NaNO2 during salami processing. In the postripening stage, the starter culture influenced the concentration of the palmitic, oleic, vaccenic, and γ-linolenic TFAs, whereas the metmyoglobin concentration was lower (which could be related to the antioxidant effect of the starter culture). In this stage, an increase in enthalpy, specific heat, and onset temperature was found when adding starter culture and NaNO2, which is directly related to polyunsaturated TFA. However, when adding just the starter culture without 50 ppm NaNO2, the E. coli population was reduced in 4 log CFU/g. This study proposes the analysis of changes in meat product processing like salami in a holistic form, where the application of starter culture with low nitrite concentrations could be in the meat industry an upward trend for reducing this additive.